IMPLEMENTASI PROGRAM DAERAH PEMBERDAYAAN MASYARAKAT (PDPM) DI KOTA PALU - Aril, Andi (Katalogis, 2015)
The Community Empowerment Local Program Implementation in Palu City. This research aims at finding out the development of the community empowerment local program policy in Palu. This is a qualitative research with descriptive research method and the techniques of the data colletion are observations, interviews, and documentations. This research employs purposive technique and 6 informanst are chosen. The result of this research indicates that implementation of the program has been running well. The results showed under the community empowerment local program policy in Palu with Michal Goggin approach implementation model results show that is not optimal, it can be seen from several aspects which Â influence it, such as : 1. The community empowerment local program Implementation in Palu City, from the aspect of supporting and upper and lower level, affected among others the availability of regulatory implementation of the program has been good, the availability of resources has not been adequately fund programs, social and political conditions of implementing the program is adequate. 2. The community empowerment local program Implementation in Palu City, from the aspect of resources and executive personnel at lower levels have not been adequate, especially with regard to infrastructure activities. 3. The community empowerment local program Implementation in Palu City from aspects already well heeling.